Foamed aluminum filled composite material and preparation method thereof
By using laser punching or punching holes in foam aluminum material and filling polyurethane or rubber, the problem of insufficient energy absorption efficiency and reusability of foam aluminum-filled composite materials under high-strength impact is solved, and a higher Interface compatibility and overall performance.
Patent Information
- Application Number
- CN202411252557.4
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-09-09
- Publication Date
- 2024-12-31
- Estimated Expiration
- 2044-09-09
AI Technical Summary
The existing foam aluminum-filled composite materials are limited in energy absorption efficiency and reusability under high-strength impact, resulting in interface incompatibility problems, affecting their long-term reliability in high-energy absorption application scenarios.
Laser drilling or punching drilling method is used to form through holes in aluminum foam material, and molten polyurethane or rubber is filled into the holes through pressure filling method, combined with vacuum heating and curing treatment, forming a foam aluminum foam filled composite material filled with aluminum foam. , avoid interface incompatibility problems.
It improves the specific properties of the material, enhances the physical interlock between polyurethane or rubber and foam aluminum, improves the bonding force and overall performance of the interface, and ensures the long-term reliability of the composite material under high-strength impact.
Smart Images

Figure BDA0005032874430000101 
Figure BDA0005032874430000111
Abstract
Description
Technical Field
[0001] The invention relates to the technical field of energy absorbing materials, and in particular to a foam aluminum filled composite material and a preparation method thereof. Background Art
[0002] Foam aluminum filled composites, as an advanced lightweight porous material, have shown great application potential in many fields due to their unique microstructure. These materials are not only lightweight, high specific strength and good corrosion resistance, but also provide excellent sound absorption, energy absorption capacity and thermal insulation. However, in order to meet the needs of a wider range of applications, especially in industries with higher requirements for thermal insulation, energy absorption and acoustic properties, such as aerospace, automotive, construction and military fields, the performance of existing foam aluminum filled composites needs to be further optimized. Although foam aluminum filled composites perform well in many aspects, there is still room for improvement in their performance. Specifically, although the energy absorption performance of foam aluminum is outstanding, its energy absorption efficiency and reusability may be limited under high-intensity impact, affecting its long-term reliability in high-energy absorption application scenarios.
[0003] Polyurethane materials usually have an open or closed microporous structure, which can absorb a large amount of energy through the deformation of the pores when impacted, similar to a spring system with many small air bags. When the polyurethane material is subjected to force, its internal chemical bonds and intermolecular forces will deform, converting kinetic energy into heat energy, thereby absorbing impact energy and slowing down the transmission of impact force. Compared with completely elastic materials, polyurethane will undergo plastic deformation when subjected to a large impact, which allows it to absorb more energy without immediately rebounding, thereby reducing the impact force transmitted to the structure or human body.
[0004] Therefore, the prior art usually produces a foam aluminum filled composite material by covering the surface of the foam aluminum material with polyurethane. For example, the patent application with application number CN201910025926.9 discloses a foam aluminum filled composite material for automobile bumpers, which is achieved by coating the foam aluminum with polyurethane. However, the surface coating method is prone to cause the interface incompatibility between polyurethane and foam aluminum, and any interface defects or poor adhesion will affect the overall performance of the composite material, especially when subjected to impact or cyclic loads. Therefore, the commonly used coating method obviously cannot meet the demand. Summary of the invention
[0005] The present invention provides a foam aluminum filled composite material and a preparation method thereof, which aims to maintain the original advantages of foam aluminum, obtain through holes in the foam composite material by laser drilling or punching, and then fill the through holes with polyurethane or rubber, so as to further enhance the specific properties of the material and avoid the interface incompatibility problem occurring in the commonly used coating method.
[0006] The first object of the present invention is to provide a method for preparing a composite material filled with foamed aluminum, the preparation method specifically comprising the following steps:
[0007] S1. A through hole is obtained in the foam aluminum material by laser punching or punching;
[0008] S2, using a pressure filling method to fill molten polyurethane or molten rubber into the through hole of step S1;
[0009] S3. Place the aluminum foam material filled with molten polyurethane or molten rubber in a vacuum chamber, increase the temperature while evacuating the chamber, and slowly release the vacuum and cool down the chamber after the curing reaction to obtain an aluminum foam filled composite material.
[0010] Compared with the prior art, the present invention obtains through holes in the foam aluminum material by laser drilling or stamping, and then fills molten polyurethane or molten rubber into the through holes, and finally heats and cures to obtain a foam aluminum filled composite material filled with polyurethane or rubber. The through holes are formed in the foam aluminum by laser drilling technology or stamping drilling method, and the size, shape and distribution of the holes can be precisely controlled, which helps to improve the uniformity of the filler and the effectiveness of the interface contact. The use of pressure filling method can ensure that the molten polyurethane or molten rubber completely fills the pores of the foam aluminum to avoid air residue, thereby enhancing the physical interlocking between the polyurethane or rubber and the foam aluminum and improving the adhesion of the interface. In summary, the entire process from drilling, pressure filling to temperature curing can improve the interface compatibility between the foam aluminum and the filling material, and ensure that the composite material has excellent performance.
[0011] In some embodiments, in step S1, the foam aluminum material is pretreated, and the pretreatment step is: covering the visible surface of the foam aluminum material except the inner surface of the through hole with a masking tape, adding epoxy resin into an atomizing spray device for atomization treatment, and then spraying the inner surface of the through hole to form a film.
[0012] Compared with the prior art, the present invention pre-treats the aluminum foam material, and the surface of the through-holes of the aluminum foam material is covered with an epoxy resin coating to form an enhanced interface, which will greatly improve the bonding performance with polyurethane or rubber. The bonding, chemical resistance and mechanical strength of epoxy resin make it an ideal intermediate layer material, which can significantly improve the overall performance of the composite material. In the final composite process, the polyurethane or rubber is tightly combined with the epoxy resin layer in the pre-treated aluminum foam through-holes to form a strong composite structure, which is suitable for application scenarios requiring high bonding strength and good mechanical properties.
[0013] In some embodiments, the power of the atomization treatment is 600-700W.
[0014] Compared with the prior art, the present invention performs atomization processing under high power conditions, which helps to generate sufficiently fine droplets to ensure the uniformity and quality of the coating.
[0015] In some embodiments, the parameters of the spraying film are as follows: flow rate is 3-5 ml / min, height is 2-3 cm, spraying speed is 15-20 mm / s, and temperature environment is 60-70°C.
[0016] Compared with the prior art, the present invention ensures that the coating is not too thick or too thin by controlling the amount of atomized resin per unit time. Too large a flow rate may lead to uneven coating or excessive accumulation, while too small a flow rate may lead to insufficient coating. Combined with the short-distance spraying height, the shorter distance helps to improve the deposition efficiency of the atomized particles and ensure the uniformity of the coating. The speed of the spray gun movement is further controlled to ensure the uniform distribution of the coating in the entire spraying area. Too fast a speed may lead to uneven coating thickness, while too slow a speed may cause excessive thickness of the local coating. In addition, the temperature is fully considered to have an important influence on the fluidity and curing rate of the epoxy resin. At a higher temperature, the resin is easier to flow, which helps to form a more uniform coating and may also accelerate the initial curing process. Combining these parameters, the atomization process and the spray film forming process are carried out under precise control to ensure that the epoxy resin forms a thin and uniform coating on the inner surface of the through hole of the foam aluminum material.
[0017] In some embodiments, in step S1, the parameters of laser drilling are as follows: current is 110-115A, pulse width is 0.4ms, frequency is 130-140Hz, and defocus is -1mm.
[0018] Compared with the prior art, the present invention adopts the above-mentioned laser drilling parameters, among which the selection of current and frequency tends to increase the production speed, while the setting of pulse width and defocus amount focuses on controlling the quality of the hole, including the smoothness and verticality of the hole wall. Through the combination of the above-mentioned parameters, the best drilling effect can be obtained.
[0019] In some embodiments, the through hole is a tapered hole, and the hole taper is 1.15-1.20°.
[0020] Compared with the prior art, the present invention adopts a tapered hole with a small hole taper, mainly because the tapered hole can increase the complex internal structure of the material. When impacted, this structure can provide more paths to disperse and absorb energy. At the same time, the present invention further limits the hole taper of the through hole, because the hole taper affects the strength, rigidity and processability of the material, and a smaller hole taper can more evenly distribute the pressure on the contact surface, avoiding excessive stress concentration, thereby extending the service life of the foam aluminum filled composite material and reducing the risk of fatigue cracks.
[0021] In some embodiments, the through holes are arranged in a square array, and s', h' and d' are obtained by the following calculation formula:
[0022] s′=s 0 -△s
[0023] h′=h 0 +αΔs
[0024] d′=d 0 +βΔs
[0025] Among them, s 0 is the hole spacing of standard parts of foam aluminum material;
[0026] h 0 is the thickness of standard parts of foam aluminum material;
[0027] d 0 is the aperture of the standard part of foam aluminum material;
[0028] s′ is the pore spacing of the through holes of the target aluminum foam filled composite material;
[0029] h′ is the thickness of the target aluminum foam-filled composite material;
[0030] d′ is the pore size of the through-holes of the target aluminum foam-filled composite material;
[0031] Δs is the difference between the hole spacing of the standard aluminum foam material and the hole spacing of the through holes of the target aluminum foam filled composite material;
[0032] α is the first preset material coefficient of the target foam aluminum filled composite material;
[0033] β is a second preset material coefficient of the target foam aluminum filled composite material.
[0034] Compared with the prior art, the present invention combines the standard parts of the foam aluminum material and the design standard (such as thickness) to be achieved by the target foam aluminum filled composite material, and combines the first preset material coefficient of the target foam aluminum filled composite material and the second preset material coefficient of the target foam aluminum filled composite material, thereby obtaining the target parameters of the through holes of the target foam aluminum filled composite material (such as hole spacing and hole diameter), thereby optimizing the performance of the target foam aluminum filled composite material. It is worth mentioning that s 0 The hole spacing formed by punching the standard parts of the foam aluminum material, d 0 The aperture formed by punching holes in standard parts of foam aluminum material.
[0035] In some embodiments, the s 0 is 0.2mm, the h 0 is 6cm, the d 0It is 0.02mm.
[0036] The present invention defines the parameters of standard parts of foam aluminum materials as a benchmark for target foam aluminum filled composite materials. By adjusting the hole spacing, thickness and pore size, key performance indicators such as sound absorption, thermal insulation, strength and stiffness of the composite materials can be optimized.
[0037] In some embodiments, the α is 10000-11000, and the β is 0.1-0.15.
[0038] The preset material coefficient is closely related to the density, expected performance (such as strength, fracture toughness, etc.) of the target foam aluminum filled composite material, as well as the type and density of the filling material. In the present invention, limiting the first preset material coefficient and the second preset material coefficient to the above range is the optimal parameter obtained by the inventor after actual experiments, which is conducive to further improving the composite performance of the target composite material.
[0039] The second object of the present invention is to provide a foam aluminum filled composite material prepared by the above preparation method. DETAILED DESCRIPTION
[0040] In order to make the above-mentioned purposes, features and advantages of the present invention more obvious and easy to understand, the specific embodiments of the present invention are described in detail below. It should be noted that the following embodiments are only used to illustrate the implementation method and typical parameters of the present invention, and are not used to limit the parameter range described in the present invention. Reasonable changes derived therefrom are still within the scope of protection of the claims of the present invention.
[0041] It should be noted that the endpoints and any values of the ranges disclosed in this article are not limited to the precise ranges or values, and these ranges or values should be understood to include values close to these ranges or values. For numerical ranges, the endpoint values of each range, the endpoint values of each range and the individual point values, and the individual point values can be combined with each other to obtain one or more new numerical ranges, and these numerical ranges should be regarded as specifically disclosed in this article.
[0042] Unless otherwise defined, all terms, symbols and other scientific terms used herein are intended to have the same meaning as those commonly understood by those skilled in the art to which the present invention belongs. In some cases, terms with conventionally understood meanings are defined herein for the purpose of clarification or ease of reference, and such definitions herein should not be construed as indicating significant differences from conventional understandings in the art. The technical methods described or cited herein are generally well understood by those skilled in the art and are adopted by conventional methods. Unless otherwise stated, the use of commercially available kits, reagents and instruments is carried out in accordance with the protocols and parameters given by the manufacturer.
[0043] The technical effects of the present invention are described below in conjunction with specific embodiments.
[0044] Example 1
[0045] The present embodiment provides a foam aluminum filled composite material, on which a plurality of through holes arranged in a square array are provided, the through holes are filled with polyurethane, the through holes are conical holes, and the hole taper is 1.15°, and the hole taper is obtained by adjusting the parameters of laser drilling.
[0046] The aluminum foam filled composite material of this embodiment is prepared by the following preparation method:
[0047] S1. A through hole is obtained in the foam aluminum material by using a laser drilling method;
[0048] S2, using a pressure filling method to fill the molten polyurethane into the through hole of step S1;
[0049] S3. Place the aluminum foam material filled with molten polyurethane in a vacuum chamber, evacuate the chamber and raise the temperature, slowly release the vacuum and cool the chamber after the curing reaction to obtain an aluminum foam filled composite material.
[0050] Among them, the size of the standard foam aluminum material is: s 0 0.2mm, h 0 6cm, d 0 0.02mm
[0051] In this embodiment, the parameters of the target foam aluminum filled composite material are: known thickness h′ is 7 cm, α is 10000, β is 0.1, s′ is 0.19 mm, and d′ is 0.021 mm.
[0052] s′=s 0 -△s
[0053] h′=h 0 +αΔs
[0054] d′=d 0 +βΔs
[0055] Among them, s 0 is the hole spacing of standard parts of foam aluminum material;
[0056] h 0 is the thickness of standard parts of foam aluminum material;
[0057] d 0 is the aperture of the standard part of foam aluminum material;
[0058] s′ is the pore spacing of the through holes of the target aluminum foam filled composite material;
[0059] h′ is the thickness of the target aluminum foam-filled composite material;
[0060] d′ is the pore size of the through-holes of the target aluminum foam-filled composite material;
[0061] △s is the difference between the hole spacing of the standard aluminum foam material and the hole spacing of the through holes of the target aluminum foam filled composite material;
[0062] α is the first preset material coefficient of the target foam aluminum filled composite material;
[0063] β is a second preset material coefficient of the target foam aluminum filled composite material.
[0064] Example 2
[0065] The present embodiment provides a foam aluminum filled composite material, on which a plurality of through holes arranged in a square array are provided, the through holes are filled with rubber, the through holes are conical holes, and the hole taper is 1.2°, and the hole taper is obtained by adjusting laser drilling parameters.
[0066] S1. A through hole is obtained in the foam aluminum material by using a laser drilling method;
[0067] S2, using a pressure filling method to fill the molten rubber into the through hole of step S1;
[0068] S3, placing the foamed aluminum material filled with molten rubber in a vacuum chamber, evacuating the chamber while increasing the temperature, slowly releasing the vacuum and cooling the chamber after the curing reaction, to obtain a foamed aluminum filled composite material.
[0069] Among them, the size of the standard foam aluminum material is: s 0 0.2mm, h 0 6cm, d 0 0.02mm
[0070] In this embodiment, the parameters of the target foam aluminum filled composite material are: known thickness h′ is 6.5 cm, α is 10500, β is 0.12, s′ is 0.15 mm, and d′ is 0.0205 mm.
[0071] s′=s 0 -△s
[0072] h′=h 0 +αΔs
[0073] d′=d 0 +βΔs
[0074] Among them, s 0 is the hole spacing of standard parts of foam aluminum material;
[0075] ho is the thickness of standard parts of foam aluminum material;
[0076] d 0 is the aperture of the standard part of foam aluminum material;
[0077] s′ is the pore spacing of the through holes of the target aluminum foam filled composite material;
[0078] h′ is the thickness of the target aluminum foam-filled composite material;
[0079] d′ is the pore size of the through-holes of the target aluminum foam-filled composite material;
[0080] △s is the difference between the hole spacing of the standard aluminum foam material and the hole spacing of the through holes of the target aluminum foam filled composite material;
[0081] α is the first preset material coefficient of the target foam aluminum filled composite material;
[0082] β is a second preset material coefficient of the target foam aluminum filled composite material.
[0083] Example 3
[0084] The present embodiment provides a foam aluminum filled composite material, on which a plurality of through holes arranged in a square array are provided, the through holes are filled with rubber, the through holes are conical holes, and the hole taper is 1.2°, and the hole taper is obtained by adjusting the parameters of stamping and punching.
[0085] S1. A punching method is used to obtain a through hole in the foam aluminum material;
[0086] S2, using a pressure filling method to fill the molten rubber into the through hole of step S1;
[0087] S3, placing the foamed aluminum material filled with molten rubber in a vacuum chamber, evacuating the chamber while increasing the temperature, slowly releasing the vacuum and cooling the chamber after the curing reaction, to obtain a foamed aluminum filled composite material.
[0088] Among them, the size of the standard foam aluminum material is: s 0 0.2mm, h 0 6cm, d 0 0.02mm
[0089] In this embodiment, the parameters of the target foam aluminum filled composite material are: known thickness h' is 5.5 cm, α is 10800, β is 0.14, s' is 0.205 mm, and d' is 0.019 mm.
[0090] s′=s 0 -△s
[0091] h′=h0 +αΔs
[0092] d′=d 0 +βΔs
[0093] Among them, s 0 is the hole spacing of standard parts of foam aluminum material;
[0094] h 0 is the thickness of standard parts of foam aluminum material;
[0095] d 0 is the aperture of the standard part of foam aluminum material;
[0096] s′ is the pore spacing of the through holes of the target aluminum foam filled composite material;
[0097] h′ is the thickness of the target aluminum foam-filled composite material;
[0098] d′ is the pore size of the through-holes of the target aluminum foam-filled composite material;
[0099] △s is the difference between the hole spacing of the standard aluminum foam material and the hole spacing of the through holes of the target aluminum foam filled composite material;
[0100] α is the first preset material coefficient of the target foam aluminum filled composite material;
[0101] β is a second preset material coefficient of the target foam aluminum filled composite material.
[0102] Example 4
[0103] The present embodiment provides a foam aluminum filled composite material, on which a plurality of through holes arranged in a square array are provided, the through holes are filled with polyurethane, the through holes are conical holes, and the hole taper is 1.15°, and the hole taper is obtained by adjusting the parameters of stamping and punching.
[0104] The aluminum foam filled composite material of this embodiment is prepared by the following preparation method:
[0105] S1. A punching method is used to obtain a through hole in the foam aluminum material;
[0106] S2, using a pressure filling method to fill the molten polyurethane into the through hole of step S1;
[0107] S3. Place the aluminum foam material filled with molten polyurethane in a vacuum chamber, evacuate the chamber and raise the temperature, slowly release the vacuum and cool the chamber after the curing reaction to obtain an aluminum foam filled composite material.
[0108] Among them, the size of the standard foam aluminum material is: s 0 0.2mm, h 06cm, d 0 0.02mm
[0109] In this embodiment, the parameters of the target foam aluminum filled composite material are: known thickness h′ is 6.8 cm, α is 11000, β is 0.15, s′ is 0.2 mm, and d′ is 0.02 mm.
[0110] s′=s 0 -△s
[0111] h′=h 0 +αΔs
[0112] d′=d 0 +βΔs
[0113] Among them, s 0 is the hole spacing of standard parts of foam aluminum material;
[0114] h 0 is the thickness of standard parts of foam aluminum material;
[0115] d 0 is the aperture of the standard part of foam aluminum material;
[0116] s′ is the pore spacing of the through holes of the target aluminum foam filled composite material;
[0117] h′ is the thickness of the target aluminum foam-filled composite material;
[0118] h′ is the pore size of the through-holes of the target aluminum foam-filled composite material;
[0119] △s is the difference between the hole spacing of the standard aluminum foam material and the hole spacing of the through holes of the target aluminum foam filled composite material;
[0120] α is the first preset material coefficient of the target foam aluminum filled composite material;
[0121] β is a second preset material coefficient of the target foam aluminum filled composite material.
[0122] Example 5
[0123] The present embodiment provides a foam aluminum filled composite material, which is different from the embodiment 1 only in that the foam aluminum material of the present embodiment is pretreated, and the pretreatment steps are: covering the visible surface of the foam aluminum material except the inner surface of the through hole with a masking tape, adding epoxy resin into an atomizing spray device for atomization treatment, and then spraying the inner surface of the through hole to form a film, wherein the power of the atomization treatment is 600W, and the parameters of the spraying film are as follows: the flow rate is 3ml / min, the height is 2cm, the spraying speed is 15mm / s, and the temperature environment is 60°C.
[0124] Example 6
[0125] The present embodiment provides a foam aluminum filled composite material, which is different from the embodiment 2 only in that the foam aluminum material of the present embodiment is pretreated, and the pretreatment steps are: the visible surface of the foam aluminum material except the inner surface of the through hole is covered with a masking tape, epoxy resin is added into an atomizing spray device for atomization treatment, and then the inner surface of the through hole is sprayed to form a film, wherein the power of the atomization treatment is 620W, and the parameters of the spraying film are as follows: flow rate is 3.5ml / min, height is 2.5cm, spray speed is 16mm / s, and temperature environment is 62°C.
[0126] Example 7
[0127] The present embodiment provides a foam aluminum filled composite material, which is different from the embodiment 3 only in that the foam aluminum material of the present embodiment is pretreated, and the pretreatment steps are: covering the visible surface of the foam aluminum material except the inner surface of the through hole with a masking tape, adding epoxy resin into an atomizing spray device for atomization treatment, and then spraying the inner surface of the through hole to form a film, wherein the power of the atomization treatment is 650W, and the parameters of the spraying film are as follows: flow rate is 4ml / min, height is 2.5cm, spray speed is 17mm / s, and temperature environment is 65°C.
[0128] Example 8
[0129] The present embodiment provides a foam aluminum filled composite material, which is different from the embodiment 4 only in that the foam aluminum material of the present embodiment is pretreated, and the pretreatment steps are: covering the visible surface of the foam aluminum material except the inner surface of the through hole with a masking tape, adding epoxy resin into an atomizing spray device for atomization treatment, and then spraying the inner surface of the through hole to form a film, wherein the power of the atomization treatment is 700W, and the parameters of the spraying film are as follows: flow rate is 5ml / min, height is 3cm, spray speed is 20mm / s, and temperature environment is 70°C.
[0130] Comparative Example 1
[0131] This comparative example provides a commercially available foam aluminum material.
[0132] Comparative Example 2
[0133] This comparative example provides a foam aluminum filled composite material, which is prepared using the technical solution of Example 1 with application number CN201910025926.9.
[0134] The performance of the composite materials obtained in Examples 1-8 and Comparative Examples 1-2 was tested, and the test results are shown in Table 1.
[0135] Table 1: Performance test results of the composite materials obtained in Examples 1-8 and Comparative Examples 1-2
[0136]
[0137]
[0138] Although the disclosure is disclosed as above, the protection scope of the disclosure is not limited thereto. Those skilled in the art can make various changes and modifications without departing from the spirit and scope of the disclosure, and these changes and modifications will fall within the protection scope of the present invention.
Claims
1. A method for preparing a composite material filled with aluminum foam, characterized in that: The preparation method specifically comprises the following steps: S1. A through hole is obtained in the foam aluminum material by laser punching or punching; S2, using a pressure filling method to fill molten polyurethane or molten rubber into the through hole of step S1; S3. Place the aluminum foam material filled with molten polyurethane or molten rubber in a vacuum chamber, increase the temperature while evacuating the chamber, and slowly release the vacuum and cool down the chamber after the curing reaction to obtain an aluminum foam filled composite material.
2. The method for preparing the composite material filled with aluminum foam according to claim 1, characterized in that: In step S1, the foam aluminum material is pretreated, and the pretreatment step is: the visible surface of the foam aluminum material except the inner surface of the through hole is covered with a masking tape, epoxy resin is added to an atomizing spray device for atomization treatment, and then the inner surface of the through hole is sprayed to form a film.
3. The method for preparing the composite material filled with aluminum foam according to claim 2, characterized in that: The power of the atomization treatment is 600-700W.
4. The method for preparing the composite material filled with aluminum foam according to claim 2, characterized in that: The parameters of the spraying film are as follows: flow rate is 3-5 ml / min, height is 2-3 cm, spraying speed is 15-20 mm / s, and temperature environment is 60-70°C.
5. The method for preparing the composite material filled with aluminum foam according to claim 1, characterized in that: In step S1, the parameters of laser drilling are as follows: current is 110-115A, pulse width is 0.4ms, frequency is 130-140Hz, and defocus is -1mm.
6. The aluminum foam filled composite material according to claim 1, characterized in that: The through hole is a tapered hole, and the hole taper is 1.15-1.20°.
7. The aluminum foam filled composite material according to claim 5, characterized in that: The through holes are arranged in a square array, and s', h' and d' are obtained by the following calculation formula: s′=s0-Δs h′=h0+αΔs d′=d0+βΔs Wherein, s0 is the hole spacing of the standard parts of foam aluminum material; h0 is the thickness of the standard part of foam aluminum material; d0 is the aperture of the standard part of foam aluminum material; s′ is the pore spacing of the through holes of the target aluminum foam filled composite material; h′ is the thickness of the target aluminum foam-filled composite material; d′ is the pore size of the through-holes of the target aluminum foam-filled composite material; Δs is the difference between the hole spacing of the standard aluminum foam material and the hole spacing of the through holes of the target aluminum foam filled composite material; α is the first preset material coefficient of the target foam aluminum filled composite material; β is a second preset material coefficient of the target foam aluminum filled composite material.
8. The aluminum foam filled composite material according to claim 7, characterized in that: The s0 is 0.2 mm, the h0 is 6 cm, and the d0 is 0.02 mm.
9. The aluminum foam filled composite material according to claim 7, characterized in that: The α is 10000-11000, and the β is 0.1-0.
15.
10. A composite material filled with aluminum foam, characterized in that: The method is prepared by any one of claims 1 to 9.
Citation Information
Patent Citations
Preparation method of foam aluminum composite material for preparing automobile anti-collision beam
CN109575573A
Foamed aluminum composite porous material and preparation method thereof
CN103613920A
Polyurethane / foamed aluminum composite material and preparation method thereof
CN104439166A
Damping material filled foam metal embedded periodic cavity type underwater sound absorption structure
CN111696510A
Production of an open cell aluminium foam with controlled macroporosity
IN201941000384A
